EhVps35, a retromer component, is involved in the recycling of the EhADH and Gal/GalNac virulent proteins of Entamoeba histolytica - Díaz-Valdez, Joselin; Javier-Reyna, Rosario; Montaño, Sarita; Talamás-Lara, Daniel; Orozco, Esther (Frontiers in Parasitology, 2024)
The retromer is a highly conserved eukaryotic complex formed by the cargo selective complex (CSC) and the sorting nexin (SNX) dimer subcomplexes. Its function is protein recycling and recovery from the endosomes to conduct the target molecules to the trans-Golgi network or the plasma membrane. The protozoan responsible for human amoebiasis, Entamoeba histolytica, exhibits an active membrane movement and voracious phagocytosis, events in which the retromer may be fully involved. In this work, we studied the structure of EhVps35 the central member of the CSC retromeric subcomplex as it binds EhVps26 and EhVps29, the other two CSC members, allowing the position of the retromer in the membranes. We also studied the EhVps35 role in the recycling of virulence proteins, particularly those involved in phagocytosis. Confocal microscopy assays revealed that EhVps35 is located in the plasmatic and endosomal membranes and in the phagocytic cups and channels. In addition, it follows the target cell from the moment it is in contact with the trophozoites. Molecular docking analyses, immunoprecipitation assays, and microscopy studies revealed that EhVps35 interacts with the EhADH, Gal/GalNac lectin, and actin proteins. In addition, experimental evidence indicated that it recycles surface proteins, particularly EhADH and Gal/GalNac proteins, two molecules highly involved in virulence. Knockdown of the Ehvps35 gene induced a decrease in protein recycling, as well as impairments in the efficiency of adhesion and the rate of phagocytosis. The actin cytoskeleton was deeply affected by the Ehvps35 gene knockdown. In summary, our results revealed the participation of EhVps35 in protein recycling and phagocytosis. Furthermore, altogether, our results demonstrated the concert of finely regulated molecules, including EhVps35, EhADH, Gal/GalNac lectin, and actin, in the phagocytosis of E. histolytica.